Yield after intensive pruning of fertigated coffee plants subjected to different macronutrient rates - Souza, Victor Hugo Silva; Carvalho, Alex Mendonça; Teramoto, Érico; Silva, Maria Cristina de Souza; Guimarães, Rubens José (Semina: Ciências Agrárias, 2024)
Coffee cultivation holds significant importance both nationally and internationally, with Brazil standing as the leading producer and exporter of this commodity worldwide. A crucial factor for high yield is the appropriate nutrient supply, particularly following intensive pruning. This study aimed to establish fertilization guidelines for fertigated coffee trees post-recepa pruning (i.e., stumping or cutting off all plagiotropic branches at 20-30 cm from the orthotropic branch) focusing on reproductive variables and investigating the anatomical and physiological changes in plants fertilized with varying N-P-L levels. The research was conducted in Lavras, MG, Brazil, at the Coffee Production Sector of the Department of Agriculture, Federal University of Lavras (UFLA). Initiated in March 2010, the cultivation involved different fertilization intensities through fertigation, using Topázio MG-1190 cultivar seedlings. The experiment featured five fertilization levels (10, 70, 100%, 130, and 160%) relative to the standard recommendation for rainfed coffee farming. In 2015, the plants underwent "low recepa" pruning (no shoots left) and were subsequently assessed for morphology, physiology, and anatomy (2019/2020). A randomized block design was employed, arranged in a factorial scheme with split-plots over time, including three replications. This was structured as a 5Ã—2 factorial (five fertilizer levels and two harvests). The findings indicate that to attain higher yields post-recepa pruning, a minimum of 100% of the standard production fertilization is necessary, achieving yields up to 93.05 bags/ha. This requires at least 54.0 g/plant of N (450 kg/ha N), 4.0 g/plant of P2O5 (33.3 kg/ha P2O5), and 20.0 g/plant of K2O (166.7 kg/ha K2O). Plants with balanced nutrition, that is, those which receive the recommended rate, exhibit a larger ratio between polar and equatorial diameters of stomata, potentially enhancing gas exchange in coffee leaves.